Pengaruh Implementasi Internal Marketing Terhadap Kinerja Melalui Kepuasan Tenaga Kependidikan Di Fakultas Ekonomi Dan Bisnis Universitas Brawijaya Malang - Ikhsania, Zulfa (Jurnal Ilmiah Administrasi Publik, 2015)
The study aims to analyze positive influence of internal marketing implementation in boosting educational personnel satisfaction, the positive influence of satisfaction improve the performance of staff, the positive effect of the implementation of internal marketing improve the performance of educators in FEB UB Malang. Population 103 staff, testing three hypotheses with Structural Model PLS. Implementation of internal marketing directly affect significantly increase the satisfaction of educators. Satisfaction educators effect but not significantly improve the performance of educators. Internal marketing effect, but did not significantly improve the performance of educators.